DECAPITATION INJURIES ON RAILWAYTRACK (Journal of Forensic Medicine & Toxicology, 2018)
Objectives: Decapitation or complete severance of head from the body is imminently a fatal condition and is commonly encountered in railway accidents predominantly associated with  decapitation by wheels of trains or with postmortem dismemberment following homicide. Deaths with decapitation lead to a complex forensic investigation in which the forensic  pathologist plays a major role as a point of reference in the execution of a full and correct inquest. A differentiation between decapitation due to suicide, accident, homicide or mutilation  of a body after death by another cause on autopsy. Methods: Three case reports with decapitation of head of which two incidents occurred involving  the fall on railway track and one of the victims committed suicide by jumping from Delhi Metro train.
Keywords: Decapitation; Railway accident; suicide